2022
DOI: 10.3389/fimmu.2022.903513
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell RNA Sequencing Unravels Distinct Tumor Microenvironment of Different Components of Lung Adenocarcinoma Featured as Mixed Ground-Glass Opacity

Abstract: Lung adenocarcinoma featured as mixed ground-glass opacity (mGGO) doubled its volume half of the time in comparison with that featured as pure ground-glass opacity (pGGO). The mechanisms underlying the heterogeneous appearance of mGGO remain elusive. In this study, we macro-dissected the solid (S) components and ground-glass (GG) components of mGGO and performed single-cell sequencing analyses of six paired components from three mGGO patients. A total of 19,391 single-cell profiles were taken into analysis, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…CD47, a classic immune escape molecule, prevents immune cell maturation and the release of immune activation factors through the CD47-SIRPA axis. A scRNA-seq study further confirmed that CD47 and SIRPA were upregulated in lung cancer compared to normal lung tissue (51). Additionally, it was found that CD24 was found to be generally elevated in the epithelial cells of lung cancer.…”
Section: Bidirectional Regulation Between Tumor and Stromal Cellsmentioning
confidence: 69%
See 2 more Smart Citations
“…CD47, a classic immune escape molecule, prevents immune cell maturation and the release of immune activation factors through the CD47-SIRPA axis. A scRNA-seq study further confirmed that CD47 and SIRPA were upregulated in lung cancer compared to normal lung tissue (51). Additionally, it was found that CD24 was found to be generally elevated in the epithelial cells of lung cancer.…”
Section: Bidirectional Regulation Between Tumor and Stromal Cellsmentioning
confidence: 69%
“…Accumulating scRNA-seq studies have identified several representative subsets of TAMs in NSCLC, defined by the symbolic markers complement 1 q (C1Q), SPP1, triggering receptor expressed on myeloid cells-2 (TREM2), NLRP3, LYVE1 (48)(49)(50)(51)(52). Protumorigenic macrophages consist of C1Q + , SPP1 + , and TREM2 + subsets (48,49,52,53).…”
Section: New Advances In Defining Tam Subsetsmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, epithelial cells showed extremely high inter-tumor heterogeneity ( Figure 2 A), similar to the findings of previous studies. 13 , 14 , 15 Therefore, we attempted to identify malignant cells in the epithelial cell population through CopyKAT inference in a case-by-case manner. We obtained1355 (A304-01), 2071 (A304-02), 1542 (A304-03), and 716 (A304-04) malignant epithelial cells from the epithelial cell types ( Figure 2 B).…”
Section: Resultsmentioning
confidence: 99%
“…From the Gene Expression Omnibus (GEO) database, scRNAseq data (GSE203360) and microarray expression profiles (GSE31210) of LUAD samples were accessed (10)(11)(12). From the Cancer Genome Atlas (TCGA) database, Bulk RNA-seq data (transcripts per million, TPM) of LUAD samples were obtained on the Sangerbox platform (13,14).…”
Section: Data Collection Of Luad Samplesmentioning
confidence: 99%